Peramalan Jumlah Ikan Tuna/Madidihang (Yellowfin tuna) yang Didaratkan di PPS Kutaraja Kota Banda Aceh dengan Metode Triple Exponential Smoothing - Muhammad Haikal Nasution; Samsul Anwar; Aida Fitri; Aja Fatimah Zohra (Samakia : Jurnal Ilmu Perikanan, 2019)
The Kutaraja Ocean Fisheries Port (PPS) located in Banda Aceh City is central to the fisheries sector in Aceh Province. Various types of fish have been landed at Kutaraja PPS, one of which is tuna/madidihang (yellowfin tuna). Tuna is not only in demand by the local market, but also international markets, especially Japan and America. This study aims to estimate the amount of tuna/madidihang (yellowfin tuna) production landed at Kutaraja PPS in 2018 and 2019. These estimates can help the Aceh Government in controlling the ordering of tuna/madidihang (yellowfin tuna) from within and outside the country, so that the number of tuna/madidihang (yellowfin tuna) caught and ordered can be balanced so that stock control can run well. The forecasting method used in this study is the Triple Exponential Smoothing method by using monthly data on the amount of tuna/madidihang (yellowfin tuna) production landed at Kutaraja PPS from January 2010 to December 2017. Based on the results of forecasting with the best models, the amount of tuna/madidihang (yellowfin tuna) production will landed in the Kutaraja PPS in 2018 and 2019 are predicted to be 2,395,615.8 Kg and 2,451,207.5 Kg respectively.